Phase transformations in Mo-doped FINEMETs - Silveyra, Josefina María (2010)
In this paper, the phase transformations occurring during the crystallization process of FINEMETs in which Nb has been gradually replaced by Mo have been studied by a variety of techniques including DSC, DTA, TGA, XRD and TEM. The thermal stability of the alloy was deteriorated as a consequence of Mo’s smaller atomic size. The gradual replacement of Nb by Mo reduced the onset temperature of Fe–Si and of the borides. The Curie temperature of the amorphous phase slightly decreased from 594 K for x=0 to 587 K for x=3. The borides compounds Fe2B and Fe23B6 as well as the (Nb,Mo)5Si3 phase were found to precipitate in the second and third crystallization.